1973
DOI: 10.1037/h0035372
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory and coding strategies in the deaf.

Abstract: This thesis investigates short term memory processing in orally and manually trained deaf children, as well as in hearing controls. The first two experiments used visual presentation of four-and five-letter sequences. Results were analyzed in terms of the rehearsal strategies, encoding processes and confusions. The results showed not only that the deaf were inferior to the heari.ng, but that they encoded verbal material differently. Both deaf groups, in contrast to the hearing group who relied mainly on articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 52 publications
(103 reference statements)
3
22
0
Order By: Relevance
“…Two studies, one by Conrad and Rush (1965) and another by Wallace and Corballis (1973), examined short-term retention by deaf subjects with manual language experience (and published the raw confusion matrices needed here). Of these two, only the one by Wallace and Corballis included, in the stimulus set, a high proportion of letters found by our techniques to be manually similar."…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, one by Conrad and Rush (1965) and another by Wallace and Corballis (1973), examined short-term retention by deaf subjects with manual language experience (and published the raw confusion matrices needed here). Of these two, only the one by Wallace and Corballis included, in the stimulus set, a high proportion of letters found by our techniques to be manually similar."…”
Section: Resultsmentioning
confidence: 99%
“…The first is the use of phonetic coding among the deaf subjects. Previous research has indicated that deaf subjects who do not show evidence of the use of phonetic coding tend to recall fewer items than hearing subjects who do use phonetic coding (e.g., Conrad & Rush, 1965;Wallace & Corballis, 1973). The accuracy of deaf subjects may also be less even when phonetic coding is used, although there is evidence that as deaf subjects' use of phonetic coding increases, their temporal recall accuracy improves (Conrad, 1979;Hanson, 1982;Hanson & Lichtenstein, 1990).…”
Section: Recall Of Order Informanon 607mentioning
confidence: 99%
“…Evidence consistent with this claim has been obtained repeatedly (for a review, see Cumrning & Rodda, 1985). In tasks requiring the serial recall of linguistic stimuli (whether words, digits, signs, fingerspelling, or pictures), deaf subjects have consistently been found to recall fewer items than hearing subjects, even when confounds with spatial order recall have been eliminated (e.g., Bellugi, Klima, & Siple, 1975;Blair, 1957;Hanson, 1982;Krakow & Hanson, 1985;McDaniel, 1980;Pintner & Paterson, 1917;Wallace & Corballis, 1973;Withrow, 1968). However, in the temporal recall of nonsense stimuli, deaf subjects have not been found to recall fewer items than hearing subjects (McDaniel, 1980;Olsson & Furth, 1966).…”
Section: Ibm Research Division Thomas J Watson Research Center Yormentioning
confidence: 99%
“…In general, when congenitally, profoundly deaf individuals perform a task that calls for ordered recall of English words or letters, they do not perform as well as hearing subjects (Belmont & Karchmer, 1978;Belmont, Karchmer, & Pilkonis, 1976;Hanson, 1982;MacDougall, 1979;Wallace & Corballis, 1973). Belmont and Karchmer argued that the generally poorer performance of deaf individuals reflects a "mismatch" between the native language (ASL) and the language of the information to be recalled (English).…”
Section: Accuracy Of Recallmentioning
confidence: 99%